Pesticidler hám olardıń aqıbetleri haqqında - Qosnazarov, K.A; Temirbekov, O; Ermakova, I.R (SCIENCE and SOCIETY, 2021)
The article discusses anthropogen factors which impact on nature of Aral Sea territory and environment. Therefore the mentioned factors rapidly changes enviroument and create catastrophic situations. These changes are not just ecological problem of Aral Sea territo- ry it is also the ecological problem of all people of the world.
Keywords: pesticides; ecology; nature; irrigation; land reclamation; chemical elements